TRENDS IN ASSURING THE QUALITY OF VOCATIONAL EDUCATION IN BELGIUM (Comparative Professional Pedagogy, 2025)
The article analyzes key trends in Belgian vocational education quality. The Belgian education system is organized as a complex federal structure. The system is actively engaged in integrating pan-European trends into the quality assurance of its vocational and professional education. European Quality Assurance Reference Framework for Vocational Education and Training (EQAVET) improves the quality of vocational education through planning, implementation, evaluation and adjustment. Decentralization and autonomy of vocational education institutions represent a key trend. There are federal distinctions between the Flemish and French-speaking communities. Their educational institutions autonomously develop quality assurance systems. They customize them for labor market needs. Focusing on learning outcomes, this trend aligns with the Europe-wide movement to prioritize practical knowledge and skills in graduates. The growing autonomy of institutions carries with it a responsibility for educational quality, serving as the foundation for external assessments. External evaluation and accreditation function as internal systems for quality control and assurance. Effective monitoring and decision-making in quality assurance actively leverage data and indicator analysis, encompassing graduate employment. The quality of education depends on the professional development of teachers. Internationalization and mobility enhance the quality of education, facilitate the exchange of experience, and foster the development of intercultural skills. Digitalization is a key transformative trend. It transforms teaching and learning methodologies, monitoring and evaluation processes, as well as the accessibility and flexibility of vocational education. Belgium's vocational education quality assurance systemintegrates European standards, stakeholders, teacher upskilling and digitalization.Prospects for further research into the in-depth study of the quality assurance system for vocational education in Belgium are identified.
Keywords: vocational education; Belgium; Flanders; quality assurance; EQAVET; dual learning; competence; digitalization; trends